Transcriptional reprogramming caused by cold acclimation in Meloidogyne incognita eggs - Wang, Yuanzheng; Chen, Zhijie; Yang, Yiwei; Zhang, Feng (Genes & genomics, 2021)
Background Egg hatching in Meloidogyne incognita is a highly regulated developmental event and is strictly correlated with temperature. It has been demonstrated that exposure of M. incognita eggs to low temperature seriously affects their embryonic development. On the other hand, clear evidence has shown that M. incognita is able to overwinter at subzero soil temperatures in certain open fields. Therefore, subtle physiological and genetic adaptations may occur in M. incognita to minimize freezing injuries. Objective A growing body of evidence indicates that cold acclimation plays a large role in an individual organism’s ability to cope with freezing-induced cellular damage. Given the decreasing temperatures in late autumn or early winter, we hypothesize that natural cold acclimation occurring during these periods may assist M. incognita in overwintering. Methods Transcriptomic analysis and functional enrichment analyses were used to identify and annotate differentially expressed genes (DEGs) in acclimated eggs. The expression of DEGs involved in signal transduction and protein assembly was subsequently validated by reverse transcription quantitative PCR (RT-qPCR). Results Relatively long-term preacclimation at 4 °C significantly accelerated the hatching of M. incognita eggs that were subjected to freezing at − 1 °C. Using a transcriptomic approach, we further identified 686 and 460 up- and downregulated transcripts, respectively, in pre-cold-acclimated eggs. Additionally, we used Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology annotations for functional enrichment analyses of the differentially expressed genes (DEGs). Conclusion The phenomenon in which M. incognita safely overwinters at subzero soil temperatures in certain areas may be attributed to the natural cold acclimation occurring in late autumn. Here, the identification of DEGs between acclimated and nonacclimated eggs will provide us with promising directions for future studies on the mechanisms of M. incognita freezing tolerance.